2014
DOI: 10.1007/s10144-014-0444-3
|View full text |Cite
|
Sign up to set email alerts
|

Genetic effects of living in a highly polluted environment: the case of the silversideBasilichthys microlepidotus(Jenyns) (Teleostei: atherinopsidae) in the Maipo River basin, central Chile

Abstract: Freshwater systems are one of the environments most impacted by human activity, with pollution being a highly important factor. In Chile, several rivers exhibit varied levels of pollution, one of which is the Maipo River basin where the city of Santiago is located. The silverside Basilichthys microlepidotus (Jenyns) is an endemic fish species that inhabits this basin, thus we hypothesized that pollution has affected gene diversity and migration in populations of B. microlepidotus from the Maipo River basin. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
33
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(39 citation statements)
references
References 56 publications
6
33
0
Order By: Relevance
“…It is a microphagous species, feeding on insect larvae, small invertebrates, filamentous algae and detritus (Duarte et al, 1971). It has been pointed out that it can survive in highly polluted rivers (Vega-Retter et al, 2014). Considering that B. microlepidotus is indicated as an endangered species , future conservation measures will need information about its health, stress responses and adaptive responses to human activity.…”
Section: Introductionmentioning
confidence: 99%
“…It is a microphagous species, feeding on insect larvae, small invertebrates, filamentous algae and detritus (Duarte et al, 1971). It has been pointed out that it can survive in highly polluted rivers (Vega-Retter et al, 2014). Considering that B. microlepidotus is indicated as an endangered species , future conservation measures will need information about its health, stress responses and adaptive responses to human activity.…”
Section: Introductionmentioning
confidence: 99%
“…This is not surprising, because the characteristics of the pollutants along the river are different. Vega-Retter et al (2014) showed that the two polluted sites (MEL and PEL) differ in levels of pollution, with clear differences in dissolved oxygen as well as concentrations of copper and molybdenum. Thus it is probable that pollution affects natural populations in different ways, triggering adaptation to local characteristics of the pollution even within a basin.…”
Section: Discussionmentioning
confidence: 98%
“…1). Vega-Retter et al (2014) found five different populations of silversides in this basin, two located in sites classified as highly polluted (PEL and MEL) and three populations inhabiting five sites classified as non-polluted (PU, IM, PN, MA, SFM; according to the population structure the populations are composed of PU, IM-PN and MA-SFM) according to the British Columbia Water Quality Index (BCWQI). This population structure ( Fig.…”
Section: Sampling Sites and Collectionmentioning
confidence: 99%
See 1 more Smart Citation
“…This pollution categorization was defined using the British Columbia Water Quality Index 21 based on the attainment of water quality objectives and taking into consideration the natural water quality expected at any given site. Furthermore, Principal Component Analysis indicated that the total dissolved solids, electrical conductivity, chloride, sulfate, molybdenum, ammonium, copper and nitrite were the principal variables accounting for the variance among sites 22 . Water degradation observed in the two polluted sites was the result of different contaminants, such as heavy metals from mining and factories, pesticides from agriculture and dioxins from industrial processes, among others.…”
Section: Introductionmentioning
confidence: 99%